SilE is an intrinsically disordered periplasmic ‘molecular sponge' involved in bacterial silver resistance - Asiani, Karishma R.; Williams, Huw Edward Llewelyn; Bird, Louise; Jenner, Matthew; Searle, Mark S.; Hobman, Jon L.; Scott, David J.; Soultanas, Panos (Wiley, 2016)
Ag+ resistance was initially found on the Salmonella enetrica serovar Typhimurium multi-resistance plasmid pMG101 from burns patients in 1975. The putative model of Ag+ resistance, encoded by the sil operon from pMG101, involves export of Ag+ via an ATPase (SilP), an effluxer complex (SilCFBA) and a periplasmic chaperon of Ag+ (SilE). SilE is predicted to be intrinsically disordered. We tested this hypothesis using structural and biophysical studies and show that SilE is an intrinsically disordered protein in its free apo-form but folds to a compact structure upon optimal binding to six Ag+ ions in its holo-form. Sequence analyses and site-directed mutagenesis established the importance of histidine and methionine containing motifs for Ag+-binding, and identified a nucleation core that initiates Ag+-mediated folding of SilE. We conclude that SilE is a molecular sponge for absorbing metal ions.